Teacher and student interactions and characteristics from critical theorists school - Akbar Salehi (International Journal of Evaluation and Research in Education (IJERE), 2019)
In recent years, critical thinkers have done serious discussions in education and other fields in our lives like social, cultural, political and economical. This paper is going to consider some of the critical thinkers’ theories in order to clarify teacher and student interactions in education. The research is a type of fundamental and qualitative study which frames teacher and student interactions by means of a descriptive – analytical method. Accordingly, we introduce critical teacher as a teacher who includes specific characteristics like emancipation, critical nature and openness. Therefore mentioned teacher attends the role of culture in human life and he resists reproduced by the regime. He is someone who provides the way for public hearing; in addition, he teaches his students how to resist domination. On the other side, a student in this school will not be dominated by the regime by means of its essential tools as probe and questioning. A student has been taught to hear everyone regardless of race, religion and social class. Finally, this paper proposes applying these ideas for educational systems informal and operational ways.